Emergence of rice yellow mottle virus in eastern Uganda: Recent and singular interplay between strains in East Africa and in Madagascar - Ochola, D.; Issaka, S.; Rakotomalala, M.; Pinel Galzi, A.; Ndikumana, I.; Hubert, J.; Hébrard, E.; Séré, Y.; Tusiime, Geoffrey; Fargette, D. (Elsevier, 2015)
Epidemics of rice yellow mottle virus (RYMV) have developed recently in eastern Uganda, close to Lake Victoria in East Africa. Unexpectedly, all isolates from the affected area belonged to a single strain (named S4ug), a strain that is different from the S4lv strain that has been prevalent in the Lake Victoria basin for the past five decades. Interestingly, the S4ug strain is most closely related at the genomic level (except ORF1) to the strain present in Madagascar (S4mg), 2000km away. The minor parent of the S4mg recombinant strain could not be detected. Molecular clock dating analysis indicated that the singular sequence of events - that associated the emergence of a new strain (S4ug), a modular recombination between closely related strains (S4mg and S4ug) and a long distance transmission (S4mg) - occurred recently, within the past few decades. This finding is at variance with the process of gradual strain dispersal and diversification over two centuries throughout Africa that was previously established.